Effects of the Replacement of Dietary Fish Meal with Defatted Yellow Mealworm (Tenebrio molitor) on Juvenile Large Yellow Croakers (Larimichthys crocea) Growth and Gut Health - Jian Zhang; Yanzou Dong; Kai Song; Ling Wang; Xueshan Li; Beiping Tan; Kangle Lu; Chunxiao Zhang (Animals, 2022)
This study was conducted to investigate the effects of Tenebrio molitor meal (TM) replacement for fish meal (FM) on growth performance, humoral immunity, and intestinal health of juvenile large yellow croakers (Larimichthys crocea). Four experimental diets were formulated by replacing FM with TM at different levels—0% (TM0), 15% (TM15), 30% (TM30), and 45% (TM45). Triplicate groups of juveniles (initial weight = 11.80 ± 0.02 g) were fed the test diets to apparent satiation two times daily for eight weeks. There was no significant difference in final body weight (FBW) and weight gain rate (WG) among TM0, TM15, and TM30, while TM45 feeding significantly reduced the FBW and WG. Compared with TM0, AKP activity in serum was significantly decreased in TM45, while the TM15 group remarkably increased LZM activity. TM30 showed significantly higher serum C3 levels compared to the TM0 group, while the TM addition groups decreased the C4 levels significantly in the serum. In terms of intestinal histology, the addition of TM increased the height and thickness of the intestinal villus and also increased the thickness of the intestinal muscles significantly. The addition of TM significantly reduced the serum DAO and D-lactate concentrations. The results of 16S rRNA gene sequencing showed that the addition of TM significantly enhanced the relative abundance of Bacilli and Lactobacillus and contributed to the decrease in the relative abundance of Plesiomonas. In addition, the TM30 and TM45 groups significantly reduced the abundance of Peptostreptococcaceae. Overall, our results indicated that TM could be a viable alternative protein source, 6.7% TM supplantation (replacing 15% FM) in large yellow croaker feed improved humoral immunity and intestinal health with no adverse effects on growth. Furthermore, the replacement of FM with 30% and 45% TM adversely affects growth and humoral immunity.